2019
DOI: 10.28991/cej-2019-03091286
|View full text |Cite
|
Sign up to set email alerts
|

Concrete Beams Strengthened with Jute Fibers

Abstract: Nowadays, the reinforcement of concrete with natural fibers can consider being an effectual scheme to achieve the global demand for sustainable development. Due to sustainability, bio degradability, and environmental friendly, natural fibers are preferred as compared to synthetic fibers. The present study investigated the effect of width and thickness of jute fiber strips on the mechanical properties of reinforced concrete beams (RC beams). The experimental program consisted testing of twenty-four RC beams (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Moreover, 0.4-0.5% jute fiber content was found to be optimum for concrete compressive and tensile strength [40][41][42]. The jute fibers have also found their effectiveness in strengthening the concrete beams as it improves strength values, ductility, stiffness, and toughness of concrete beams [43]. In addition, the jute fiber can also be utilized in high-strength concrete as a spalling prevention agent [44].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 0.4-0.5% jute fiber content was found to be optimum for concrete compressive and tensile strength [40][41][42]. The jute fibers have also found their effectiveness in strengthening the concrete beams as it improves strength values, ductility, stiffness, and toughness of concrete beams [43]. In addition, the jute fiber can also be utilized in high-strength concrete as a spalling prevention agent [44].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber wrapping with the addition of HDPE fillers in concrete for different proportions has a significant effect on compression strength which is shown in Figure 4(b). The width and thickness of the fabric coverage area have a significant effect on loadcarrying capacity in concrete beams strengthened with FRP (19,27) .In this study, all the faces of concrete samples were wrapped with fabric. It is observed that 0%, 0.5% 1%,1.5%,2%,2.5%, and 3% filled HDPE fiber reinforced concrete wrapped with Basalt https://www.indjst.org/ fiber increases the compressive strength by 23%, 21%, 22%, 28%,16%, 29%, and 30% respectively.…”
Section: Compression Testmentioning
confidence: 99%
“…A catastrophic failure in plain concrete was observed in the loading direction and is depicted in Figure 5(a). Enhancing the strength of concrete can be achieved by the wrapping technique, but reduced ductility was observed with this technique (15,18,19,28) . This is due to brittle failure of concrete and hence transfer of load to FRP wrapped jacket.…”
Section: Compression Testmentioning
confidence: 99%
See 1 more Smart Citation
“…A percentage increase of 68.13% was found at 28 days tensile strength using a fibre volume fraction of 0.75% [8]. The addition of fibre reinforcement to concrete has now been considered an effectual way to achieve the global demand for sustainable development, due to their sustainability, bio-degradability, and environmental friendliness, natural fibres are preferred as compared to synthetic fibres [9]. According to findings, adding 1% sisal fibre to concrete increases the compressive and shear strengths by 16.9% and 9.5%, respectively, when compared to normal concrete.…”
mentioning
confidence: 99%